<h2>ADC is another way to name it.</h2><h2 /><h3><em>Please let me know if I am wrong.</em></h3>
Answer:
B) 105.20
Step-by-step explanation:
491.60 + 157.68 - 68.44 = 581.20
Answer:
![x\hookrightarrow -1\hookrightarrow 0\hookrightarrow 1\hookrightarrow 2\hookrightarrow 3\hookrightarrow 4\hookrightarrow 5](https://tex.z-dn.net/?f=x%5Chookrightarrow%09-1%5Chookrightarrow%090%5Chookrightarrow%091%5Chookrightarrow%092%5Chookrightarrow%093%5Chookrightarrow%094%5Chookrightarrow%095)
![y\hookrightarrow 5\hookrightarrow 0\hookrightarrow -3\hookrightarrow -4\hookrightarrow -3\hookrightarrow 0\hookrightarrow 5](https://tex.z-dn.net/?f=y%5Chookrightarrow%095%5Chookrightarrow%090%5Chookrightarrow%09-3%5Chookrightarrow%09-4%5Chookrightarrow%09-3%5Chookrightarrow%090%5Chookrightarrow%095)
The curve (B) matches the graph of y=x²-4x.
![----------\\Hope \ it\;helps](https://tex.z-dn.net/?f=----------%5C%5CHope%20%5C%20it%5C%3Bhelps)
32.92 next is 27 last is 230
Step-by-step explanation:
In order to find the number of solutions, we have to expand both sides out first.
![3(x - 2) + 7x = \frac{1}{2} (6x - 2)](https://tex.z-dn.net/?f=3%28x%20-%202%29%20%2B%207x%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20%286x%20-%202%29)
First, expand 3(x-2), which will obtain 3x-6.
Next, expand (1/2)(6x-2), which gives 3x - 1.
The result at this point should be as shown below:
![3x - 6 + 7x = 3x - 1](https://tex.z-dn.net/?f=3x%20%20-%206%20%2B%207x%20%3D%203x%20-%201)
Now, we would shift all x terms to the left and all number terms to the right.
![3x + 7x - 3x = - 1 + 6](https://tex.z-dn.net/?f=3x%20%2B%207x%20-%203x%20%3D%20%20-%201%20%2B%206)
After simplifying, the final equation would be:
![7x = 5](https://tex.z-dn.net/?f=7x%20%3D%205)
This is a linear equation and it has one solution.
![x = \frac{5}{7}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B5%7D%7B7%7D%20)